2013
DOI: 10.1073/pnas.1311763110
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor (ER) β expression in oligodendrocytes is required for attenuation of clinical disease by an ERβ ligand

Abstract: Treatment of experimental autoimmune encephalomyelitis (EAE) mice with the estrogen receptor (ER) β ligand diarylpropionitrile (DPN) has been shown to have neuroprotective effects via stimulation of endogenous myelination. The direct cellular mechanisms underlying the effects of this ERβ ligand on the central nervous system are uncertain because different cell types in both the peripheral immune system and central nervous system express ERs. ERβ is the target molecule of DPN because DPN treatment fails to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 33 publications
5
58
0
Order By: Relevance
“…Using conditional gene knockout mice, we have shown that the functional beneficial effects of the less-selective ERβ agonist DPN in EAE mice are largely attributable to its action on ERβ in OL lineage cells (6). Further, increased BDNF expression in DPN-administered mice lacking ERβ in OLs is not sufficient to reduce clinical disease or demyelination or to increase the PI3K/AKT/mTOR pathway activation, although it may explain partial improvement of axonal loss and conduction (5,6). It would follow that the functional benefits of therapeutic Ind-Cl, a more selective ERβ agonist, are at least partly attributable to the drug's actions on ERβ in OL lineage cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using conditional gene knockout mice, we have shown that the functional beneficial effects of the less-selective ERβ agonist DPN in EAE mice are largely attributable to its action on ERβ in OL lineage cells (6). Further, increased BDNF expression in DPN-administered mice lacking ERβ in OLs is not sufficient to reduce clinical disease or demyelination or to increase the PI3K/AKT/mTOR pathway activation, although it may explain partial improvement of axonal loss and conduction (5,6). It would follow that the functional benefits of therapeutic Ind-Cl, a more selective ERβ agonist, are at least partly attributable to the drug's actions on ERβ in OL lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…To assess Ind-Cl effects on the potentially BDNF-mediated PI3K/Akt/mTOR pathway [also modulated by DPN (6,(19)(20)(21)] in EAE mice, CC homogenates were probed for relevant proteins Fig. 3.…”
Section: Ind-clmentioning
confidence: 99%
See 1 more Smart Citation
“…[73] In this model, DPN-treatment had no effect on peripheral auto-antigen-specific T-cell responses and did not reduce spinal cord inflammation during EAE. Though ineffective Sophie Laffont, et al Estrogen-mediated protection of EAE on inflammation, DPN-treatment was shown to protect mice from demyelination and axonal loss, and to restore motor function.…”
Section: Endogenous Estrogens and Experimental Autoimmune Encephalomymentioning
confidence: 72%
“…Though ineffective Sophie Laffont, et al Estrogen-mediated protection of EAE on inflammation, DPN-treatment was shown to protect mice from demyelination and axonal loss, and to restore motor function. [29,73] Moreover, using conditional ERβ knock-out mouse models, it was reported that DPN-conferred neuroprotection was not dependent on ERβ-signaling in astrocytes nor in neurons, suggesting a role for oligodendrocytes as the primary targets of this ERβ ligand.[74] Indeed, DPN was shown to act through ERβ-signaling in oligodendrocytes not only to prevent demyelination, but also to promote remyelination.[75] Thus, it has been proposed that such ERβ-ligands could be used in combination with anti-inflammatory drugs in MS patients. [76] Beside ERβ-ligands, evidence also exists for ERα-mediated neuroprotective effects.…”
mentioning
confidence: 99%